Compsocommosis new genus, with a new species in Vietnam, and Transfer of Mictocommosis to Archipini (Lepidoptera: Tortricidae: Tortricinae: Archipini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2015)
Compsocommosis, n. gen. (Tortricidae: Tortricinae: Archipini), is described, with one new species from Vietnam, Compsocommosis vietnamensis Heppner & Bae, n. sp. The new genus is related to the Asian genus Mictocommosis, and both are placed in the tribe Archipini.